Exercise-induced fatigue and soccer kicking performance: a systematic review and meta-analysis of performance outcomes and contextual moderators - Peng, W.; Zhang, Y.; Wang, D.; Sarmento, H.; Vilas-Boas, J. P.; Ribeiro, J. (Frontiers in Physiology, 2026)
Background: The effects of exercise-induced fatigue on soccer kicking performance remain inconsistent across studies and performance metrics, suggesting that fatigue-related impairments may depend on contextual and task-related factors.